Doris Howes Calloway: A Pioneer in Human Nutrition Research. Issue 3 (May 2022) - King, Janet C.; Kretsch, Molly J.; Butte, Nancy F.; Murphy, Suzanne P.; Yates, Allison A.; Blackburn, Mary L.
Abstract : Although the importance of diet quality was identified more than 120 years ago, it was nearly 60 years before the specific quantitative nutrient needs for humans were determined. Dr Doris Howes Calloway, a nutrition professor at the University of California in Berkeley, established a metabolic unit for studying human nutrient requirements. This article reviews the early origins of human nutrition research and the unique contributions of Dr Calloway worldwide.